AN ANALYSIS OF SPEECH ACT ON BU TEJO’S UTTERANCES AS THE MAIN CHARACTERS IN TILIK MOVIE - Fadhilah, Fadhilah; Hidayat, Didin Nuruddin; Alek, Alek (Unversitas Katolik Santo Thomas, 2021)
A movie is one of the famous media that is interesting in conveying messages to the people. Tilik movie is a short movie produced by Ravacana Films collaborating with the Culture Department of Special Region of Yogyakarta (DIY). This is viral in 2020 because it shows the culture and relates to the condition and real life of people in our society. Speech act is action carried out through language. Through speech act, people can make command, request, etc. The aim of this research to analyze the speech act used by Bu Tejo as one of the main characters in the Tilik movie. The primary sources of data were Bu Tejo’s utterances in Tilik movie. This research also used its movie script as a secondary source. In speech act, there are three types of speech acts; a) locutionary acts, b) illocutionary acts, and c) perlocutionary acts. In this research, the researcher concerns to the illocutionary acts used by Bu Tejo as the main character in the Tilik. The researchers employed the descriptive qualitative method to analyze and describe the script. The script of the Tilik movie as the data of speech acts were taken and classified according to the John R. Searle's Concept of types of illocutionary acts and supported by Austin's concept. There are two research questions, 1) what kind of illocutionary acts and 2) how many frequency distributions are used by Bu Tejo as the main character in Tilik Movie. This research results in 70 illocutionary acts found in Bu Tejo’s utterances, consisting of 41 representatives, 18 directives, and 11 expressives.